(3cJGH aj Yde GdcdGes - (3CHh GdaVd LYaQ Hf CMeO Hf YHO GdSdGes
(3ChdgG (B:s
(3hHGWd hPdc eJf def EJUa dGSjeG hbO hGabhG Ydi Gdbhd HCf gPG GdbQBf GdehLhO s
(3BNQgG (B:s
(3hGdfTGW Edi GdeaGcgI GdJi gi dPI GdYbhd hddg OQ GdTGYQ hbO cfG HYOge bdjdkG abO UGQhG Cbd ef bdjd hSdGe Ydi GdeQSdjf s
(3GdfSNI HgG MhGTs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg , JQeje s
Keywords: (3GdJhMjO hGdedd hGdfMds